FILE DIN VIAŢA UNEI BISERICI ŞI A UNUI MITROPOLIT (II) - BOLDIŞOR istoric, colaborator la Muzeul Literaturii Române „M. Kogălniceanu”, Veronica (BIBLIOPOLIS, 2020)
The author summarizes the pastoral work of G. Grosu before the Union of Bessarabia with Romania in 1918. The author described in more details its work in the years 20-30, including his election as Metropolitan of Bessarabia, the opening of the Faculty of Theology in Chisinau, visits at many churches and monasteries etc. In fact, Gurie developed various activities: religious, missionary, literacy etc. The author stops on the difficulties, objective and subjective, what is facing the Bessarabian bishop.